2022
DOI: 10.3390/medicina58050577
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise Habit on Albuminuria and Metabolic Indices in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study

Abstract: Background and Objectives: Diabetes mellitus (DM) can cause macrovascular and microvascular complications, potentially resulting in further life-threatening complications. In general, the global prevalence of type 2 DM is increasing. To date, the care of DM comprises three aspects: diet, medication and exercise; among them, exercise is the most economical. Albuminuria is associated with renal injury and the progress of chronic kidney disease (CKD). The effects of habitual exercise in patients with new onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Regular exercise can also stimulate the hydrolysis and oxidation of fat, reducing lipotoxicity and promoting glucose homeostasis while reversing insulin resistance [ 87 89 ]. Kuo et al demonstrated in a cross-sectional study that diabetics who engaged in ≥150 min of exercise per week had lower proteinuria [ 90 ]. Recent studies have also suggested that the protective effect of regular exercise on the kidneys is not dependent on blood glucose levels.…”
Section: Therapeutics For Regulating Metabolic Reprogramming In Dkdmentioning
confidence: 99%
“…Regular exercise can also stimulate the hydrolysis and oxidation of fat, reducing lipotoxicity and promoting glucose homeostasis while reversing insulin resistance [ 87 89 ]. Kuo et al demonstrated in a cross-sectional study that diabetics who engaged in ≥150 min of exercise per week had lower proteinuria [ 90 ]. Recent studies have also suggested that the protective effect of regular exercise on the kidneys is not dependent on blood glucose levels.…”
Section: Therapeutics For Regulating Metabolic Reprogramming In Dkdmentioning
confidence: 99%
“…Dietary modification was shown to activate SIRT1 and AMPK and inhibit mTOR to regulate autophagy, thereby playing a crucial role in improving DKD ( 170 , 171 ). A cross-sectional study involving 229 participants found that exercise can improve proteinuria and plasma lipids in patients with diabetes ( 172 ), and this renoprotective effect of exercise was found to be associated with activation of AMPK and inhibition of mTORC1 in Wistar fatty (fa/fa) rats ( 173 ).…”
Section: Autophagy As a Therapeutic Target In Dkdmentioning
confidence: 99%